Intra- and Interdevice Deviation of Optical Coherence Tomography Angiography - Trachsler, Stefan; Baston, Arthur Emanuel; Menke, Marcel (Klinische Monatsblätter für Augenheilkunde, 2019)
Purpose To compare 4 optical coherence tomography-angiography (OCT-A) devices for foveal avascular zone (FAZ) measurements in healthy subjects.Methods The central retinas of 24 eyes of 12 healthy subjects were scanned with 4 different OCT-A devices (Optovue RTVue-XR, Zeiss Cirrus 5000-HD-OCT, a prototype Spectralis OCT2, Heidelberg Engineering, and Topcon DRI-OCT Triton Swept-source OCT). For the Topcon, Zeiss, and Optovue devices, 3-mm and 6-mm scans were performed. The Heidelberg device only provided 4-mm scans. En-face OCT-A images of the superficial and deep capillary plexus of the macular area were generated. The FAZ areas were measured and compared.Results Twenty-four healthy eyes were included. OCT-A devices showed significant differences in FAZ measurements. The Zeiss OCT-A device measured the smallest values for foveal avascular area (mean 218.7 mm2), followed by the Optovue device (229.6 mm2), the Topcon device (239.3 mm2), and the Heidelberg device (250.4 mm2). Differences were statistically significant for following devices: Heidelberg versus Optovue (p < 0.001), Heidelberg versus Zeiss (p < 0.001), Topcon versus Zeiss (p < 0.001), and Optovue versus Zeiss (p = 0.046). For the Optovue device, FAZ measurements were significantly different between 3 mm (mean 220 mm2) and 6 mm (mean 239.3 mm2, p = 0.007) scans. All other devices showed no significant difference within scan modes.Conclusion Current OCT-A devices provide images that allow such measurements, but values showed significant differences between devices and, for the Optovue instrument, even within scan modes. The data for OCTA measurements cannot be transferred interchangeably between the devices. Therefore, a patient should always be measured with the same device.
Keywords: OCT-angiography; optical coherence tomography; foveal avascular zone